The Epistemology Of Jürgen Habermas's Critical Theory - Emilia Sahira; Nasiwan Nasiwan (Riviera Publishing, 2025)
This article discusses the epistemology of critical theory, focusing on the thought of Jurgen Habermas as a representative of the second generation of the Frankfurt School. Epistemology, the study of knowledge, plays central role understanding knowledge is formed, disseminated, and used in social contexts. this context, Habermas critiques positivism and emphasizes the importance of communicative rationality and the public sphere as a means to achieve valid knowledge. He distinguishes between three types of knowledge: technical, practical, emancipatory, each which serves to understand and change social reality. Through discourse theory, Habermas emphasizes that social norms and legitimacy must be generated through an inclusive deliberative process, in which all voices are heard equally. The article also explores criticisms of Habermas's epistemology, including postmodernist views that challenge the ideal of communication free from domination. The methodological approaches used are literature review and qualitative analysis of the main philosophical works of the Frankfurt School and Habermas, as well as discourse analysis to understand the relationship between knowledge and power in society. Thus, Habermas’s critical theory epistemology offers relevant framework for understanding the dynamics of power and knowledge in modern societies, as well as its implications for law, media, and education. Other implications include the development of responsive public policies and intercultural dialogue to strengthen cooperation. this study not only provides a theoretical understanding of the epistemology critical theory, but also offers practical guidance for the application of these concepts in a broader social context, contributing to the creation of a more just democratic society.